BANGKOK CHICKEN SPERM QUALITY DURING STORAGE USING KA-EN 3B EGG YOLK DILUENT SUPPLEMENTED WITH RESVERATROL - Fattah, Abdul Hakim; Khaeruddin, Khaeruddin; Sasa, Lusi Yunita; Budianto, Rachmat (Jurnal Kedokteran Hewan, 2023)
The objective of this study was to determine the effect of resveratrol supplementation in KA-EN 3B-egg yolk dilution on sperm quality of Bangkok chickens. The semen was collected from 2 adult male Bangkok chickens with an age of 12 months and a body weight of 2.5 kg. The collected semen was divided into 5 treatments with 5 replicates each. The treatments used were KA-EN 3B-egg yolk (KEY), KEY + 0.02% resveratrol, KEY + 0.04% resveratrol, KEY + 0.06% resveratrol, and KEY + 0.08% resveratrol. The parameters observed were sperm motility, viability, and abnormalities during 24 hours, 48 hours, and 72 hours of storage in the refrigerator. The results showed that resveratrol supplementation in the diluent had no effect (P0.05) on sperm motility, viability, and abnormalities during storage. This study concluded that supplementation of resveratrol in KA-EN 3B-egg yolk diluent did not affect the quality of Bangkok chicken sperm during storage.